Effect of Toddlers' Daily Toilet Training Program Based on Developmentally Appropriate Practice Approach on Toilet Training Duration - Parvaneh Khorasani; Azam Tangestani; Maryam Maroufi (Golestan University of Medical Sciences, 2022)
Background: One of the main responsibilities of the parents is training toddlers how to control urination. Developmentally Appropriate Practice (DAP) is a useful method of toilet training for children. Video modeling is an important tool for teaching new motor skills to both children and adults. The purpose of this study was to determine the effect of Toddlers' Daily Toilet Training (TDTT) based on DAP on duration of toilet training in toddlers. Methods: This quasi-experimental field trial was conducted in healthcare centers of Isfahan, Iran, in 2018-2019. Overall, 130 pair of mothers and their 18-24 months old infants were recruited using multi-stage sampling. The subjects were then divided into a control (n=75) and an intervention (n=55) group by random assignment. At the beginning of the DAP-based approach, the subjects were assessed every 2-4 weeks in terms of readiness for toilet training by using the Child and Mother Readiness Assessment Checklist. After achieving 80% score in the checklist, the mothers in the intervention group participated in TDTT program, while the control group received no intervention. For both groups, another checklist was completed every two weeks to determine toilet training duration and time to achieve urination control. Data analysis was carried out in SPSS18 software using the independent t-tests, Chi-square test, and Mann-Whitney test at significance level of 0.05. Results: The mean duration of daily urination control in the control group (43.6±22.58 days) was significantly longer than in the TDTT group (28.71±12.12 days) (P=0.02). The age of readiness in both group ranged from 21 to 27 months. The duration of urination control was significantly associated with the mother's level of education (P=0.04) but inversely related to the age of achieving readiness (P=0.03) and the mother's employment status (P=0.05). Conclusion: Based on the results, the TDTT program using video modeling and the DAP approach is effective in shortening the duration of toilet training in toddlers.